Effect of management systems, practices, flock size, and age group on the growth performance of chicks from local chickens’ farmers - Kelvin Ngongolo; Andrew Chota (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2021)
The improved growth performance of chicks determines the production efficiency of chicken to local chicken farmers. Little has been done to understand the contribution of management systems and practices to the growth performance of chicks from farmers who are involved in rearing local chickens in Dodoma. We focused on assessing how the growth performance of chicks (length and weight) from local chicken farmers is affected by management systems (Free range and semi-intensive systems), management practices such as water provision, supplement feeding, regular cleaning, flock size, and size of banda (hut) used to raise chickens. Data were collected for 8 rounds within 2 months (once per week) from 5 farmers in three wards: Nkuhungu (n=2), Mbwanga (n=2), and Mtube (n=1). In each round, data were collected from 10 chicks per farmer (n=400 chicks for all 8 rounds and 5 farmers). Kruskal Wallis was used to determine the variation in growth performance while generalized linear model was used to assess the effect of flock size, management system on the growth performance of chicks. Growth performance was significantly increased and affected by age (P<0.05). The management system significantly contributed to the growth performance of the chicks (P<0.001). In addition, the small size of the banda (hut) with large flock size reduced the growth performance of chicks due to increased competition in terms of space, supplements, water supplied, feed provided, and treatment (P<0.05). In raising local chicken, local farmers need to be concerned in applying management practices such as supplement feeding, treatment, flock size and size of huts.